Service Analysis at the Habiburrahman Grand Mosque Library Indonesian Aerospace - Hanifatunnisa, Najwa Auliana; Sukaesih, Sukaesih; Sujana, Lusi Romaddyniah (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to (1) determine the types of user services available at the Habiburrahman Grand Mosque Library Indonesian Aerospace (2) to find out the service system adopted by the Habiburrahman Grand Mosque Library Indonesian Aerospace (3) to find out the procedures for registering new members and the rules imposed in the Library of the Great Mosque of Habiburrahman Indonesian Aerospace. This research was conducted using descriptive qualitative research methods with data collection techniques such as literature studies, interviews, observations, and documentation. The results of this study show that the Habiburrahman Grand Mosque Library Indonesian Aerospace has 8 types of user services, including user education services and information literacy training, reading rooms, circulation of library materials, references, photocopies, literature searches, online catalogs, and audiovisual (AV) collections. The library service system is mixed or mixed access. For visitors who want to get these various services, especially circulation services, then they need to register themselves first as members. The member registration procedure begins with preparing certain requirements, then filling out the form as well as paying the member's dues fee. Meanwhile, there are also 8 unwritten regulations stipulated as rules in the Library of the Great Mosque of Habiburrahman Indonesian Aerospace. An interesting finding lies in the architectural design that presents the typical nuances of the Indonesian ancient mosque.